2019
DOI: 10.3389/fevo.2019.00462
|View full text |Cite
|
Sign up to set email alerts
|

Predator Control Needs a Standard of Unbiased Randomized Experiments With Cross-Over Design

Abstract: Rapid, global changes, such as extinction and climate change, put a premium on evidence-based, environmental policies and interventions, including predator control efforts. Lack of solid scientific evidence precludes strong inference about responses of predators, people, and prey of both, to various types of predator control. Here we formulate two opposing hypotheses with possible underlying mechanisms and propose experiments to test four pairs of opposed predictions about responses of predators, domestic anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 87 publications
0
60
0
Order By: Relevance
“…This hypothesis is supported by four quantitative surveys of residents of Wisconsin from 2001 to 2013 and two qualitative focus groups from 2011 to 2012, which revealed increased inclinations to poach after Wisconsin wolf policies liberalized killing 24,25 . Three critiques of the 'facilitated poaching' hypothesis were published, and one critique of the 'frustration' hypothesis, so the scientific debate is lively but it remains based on indirect evidence and weak to moderate strengths of inference 26 .…”
mentioning
confidence: 99%
“…This hypothesis is supported by four quantitative surveys of residents of Wisconsin from 2001 to 2013 and two qualitative focus groups from 2011 to 2012, which revealed increased inclinations to poach after Wisconsin wolf policies liberalized killing 24,25 . Three critiques of the 'facilitated poaching' hypothesis were published, and one critique of the 'frustration' hypothesis, so the scientific debate is lively but it remains based on indirect evidence and weak to moderate strengths of inference 26 .…”
mentioning
confidence: 99%
“…Several approaches can be used to address human–carnivore conflicts, including the following: fully engaging key stakeholders; testing and adapting predation reduction methods and social conflict mitigation strategies; and working closely with the affected local communities (Zarco‐González et al 2018, Ohrens et al 2019a). Several recent reviews concurred in concluding that there are wide gaps in the scientific evidence on the effectiveness of techniques to reduce livestock depredation (Eklund et al 2017, van Eeden et al 2018b, Treves et al 2019). Concurrently, the list of potential strategies mentioned in the literature we reviewed is comprehensive, but most of the studies suggested mitigation techniques based exclusively on researchers’ opinions or on simple observations of the practices adopted in the StAs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a metaanalysis of evidence-based effectiveness of different interventions used to protect livestock from felids can be an important contribution enabling to better understand what works and what does not for the species of interest. We agree that the requirement for robust study designs is important (Ohrens, Bonacic, & Treves, 2019;Treves, Krofel, Ohrens, & Van Eeden, 2019), but believe that it should not be an obstacle for the meta-analyses when conditions are not optimally met. Restricting ourselves to the best available data greatly reduces the sample size and adds geographical, selection and publication biases (Haddaway, Woodcock, Macura, & Collins, 2015).…”
mentioning
confidence: 85%